Menguak Nilai-Nilai Kedamaian Dalam Musyawarah (Telaah Terhadap Kisah Politik Ratu Balqis Didalam Tafsir Al-Munir Wahbah Al-Zuhaili) - Ahmad Fadhil Rizki; Sudirman M. Johan; Afrizal Nur (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The Phenomena that occur at this time are very detrimental to society, namely conflicts and wars that occur at every point in the world since ancient times until now it will never end and will continue until the future because there is no solution in it, but in the Al-Quran, Allah SWT told a story about the politic of Balqis in the letter Al-Naml verses 32-35, namely a queen who was able to solve the war problems that would be faced with good and wise when getting a letter from the Prophet Sulaiman as containing invitation to believe in Allah SWT or will be fought if refused it, she was not in a hurry in making decision. First, she held a deliberation with her dignitaries to get the best suggestions and opinions, Second, think carefully even though she had a large amount, complete weapons and trained troops, but she also thought about the risks that would be faced after the war, Third, taking lessons from previous historical experience if the kings have fought and won, they would ruin the place and hold people to be their slaves. Fourth, from the deliberation, she considered sending a gift to the Prophet Sulaiman to change his decision, Fifth, after careful consideration, the queen of balqis decided to make peace because if she made a wrong decision the people of Sabaq would become victims of the war, from the story above, it can be concluded that the deliberation is a solution for the people to achieve the best consideration, mutual agreement and bring peace to each community and country.